Redealing the Cards: How the Presence of an Eco-Industry Modifies the Political Economy of Environmental Policies - Joan Canton (Fondazione Eni Enrico Mattei (FEEM), 2007)
An incumbent government maximizes its chances of being reelected. Its objective function encompasses both social welfare and political contributions. Its only instrument is a pollution tax. In an open-economy context, we introduce an eco-industry in addition to lobbies of polluting firms and environmentalists. Not only does the eco-industry lobby add a new political contribution toward a higher environmental tax, it also modifies the incentives of the usual lobbies. When the foreign environmental policy is constant, environmentalists can be in favor of a decrease in the local tax in order to reduce foreign pollution. It could also be in the interest of a vertical industrial pressure group to lobby toward more stringent environmental policy. In general, the impact of lobbying activities on the politically optimal tax is ambiguous as pressure groups push in different directions.
Keywords: H23; D72; 330; Eco-Industry; Environmental Taxation; Lobbies; Political Economy